2021
DOI: 10.3389/fcell.2021.692020
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Genes From Aging Pathways May Influence Human Lifespan and Improve Animal to Human Translation

Abstract: A major goal of aging research is identifying genetic targets that could be used to slow or reverse aging – changes in the body and extend limits of human lifespan. However, majority of genes that showed the anti-aging and pro-survival effects in animal models were not replicated in humans, with few exceptions. Potential reasons for this lack of translation include a highly conditional character of genetic influence on lifespan, and its heterogeneity, meaning that better survival may be result of not only acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Previously, we showed that longest-lived individuals reach peak values of weight/BMI and start to decline later in their lives, as compared to people with conventional lifespan (Yashin, et al 2013; Yashin, et al 2016). The ability to grow in size and postpone weight loss till older ages may also correlate with better physical resilience to life stressors, which is essential for survival at the oldest old ages (Ukraintseva et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that longest-lived individuals reach peak values of weight/BMI and start to decline later in their lives, as compared to people with conventional lifespan (Yashin, et al 2013; Yashin, et al 2016). The ability to grow in size and postpone weight loss till older ages may also correlate with better physical resilience to life stressors, which is essential for survival at the oldest old ages (Ukraintseva et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is somewhat logical that variants affecting genes participating in a certain pathway relevant for a given outcome may interact to enhance the effect produced by a single SNP. Indeed, it has repeatedly been shown how interactions between SNPs in aging pathways and other routes may influence CV risk more profoundly than individual SNPs in those same genes do 15 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the joint effect of different markers through gene–gene interactions further added insights into the genetic architecture of LOAD. Among the significantly interacting genes, PTPN1 (protein tyrosine phosphatase non‐receptor type 1, IIS pathway), TXNRD1 (thioredoxin reductase 1; stress response), and IGF1R (insulin‐like growth factor 1 receptor; IIS) were already found in combinations affecting survival to old age (Dato et al, 2018 ; Ukraintseva et al, 2021 ). PTPN1 and TXNRD1 were engaged in best risk combinations for longevity, respectively, with IGF1R and TP53 (DNA repair), while IGF1R , interacted with TP53 and TGFBR2 (cell proliferation).…”
Section: Discussionmentioning
confidence: 99%